Problems of Computer Technologies with Drawing - Islomovna, Mamurova Dilfuza (International Journal of Psychosocial Rehabilitation, 2020)
The use of computer technology in the educational process helps to increase students’ intellectual abilities based on information technology. The issue of "drawing" based on pedagogical technologies, the technology of computer training, the creation of electronic forms of training. The organization of computer training and the development of electronic forms of training will ensure the effective achievement of the objectives of the educational technology in the educational process. Improvement of the content, forms and methods of traditional education, taking into account the advantages of computer technologies, the development of scientific and methodological bases for the use of fast, high-quality, active and advanced methods of teaching, including computer technologies, computer science education. can develop.